2014
DOI: 10.1177/0883073814521298
|View full text |Cite
|
Sign up to set email alerts
|

Toe Walking in Autism

Abstract: Toe walking has been associated with language disorders and autism. To better understand the association between persistent toe walking and sensory and motor variables in children with autism, the degree of toe walking was compared with an estimate of the severity of sensory integration dysfunction symptoms and the presence of residual components of the tonic labyrinthine in supine reflex pattern in 61 children younger than 37 months of age with newly diagnosed autism. There was no association between the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Infant fine motor skills in ASD-assessed via parent report and standardized assessment-have been linked to concurrent and future communication, especially to characteristics of language production (Gernsbacher et al, 2008;Hellendoorn et al, 2015;Leonard et al, 2015;MacDonald et al, 2013). A similar pattern is observed for gross motor ability: Better scores on gross motor assessments are associated with better communicative ability (Bedford, Pickles, & Lord, 2015;Leonard et al, 2015;MacDonald et al, 2013;Pusponegoro et al, 2016) albeit, with one exception (Accardo & Barrow, 2015). Notably, one study found that this relation held even after controlling for nonverbal IQ .…”
Section: Motor and Communication Developmentmentioning
confidence: 85%
“…Infant fine motor skills in ASD-assessed via parent report and standardized assessment-have been linked to concurrent and future communication, especially to characteristics of language production (Gernsbacher et al, 2008;Hellendoorn et al, 2015;Leonard et al, 2015;MacDonald et al, 2013). A similar pattern is observed for gross motor ability: Better scores on gross motor assessments are associated with better communicative ability (Bedford, Pickles, & Lord, 2015;Leonard et al, 2015;MacDonald et al, 2013;Pusponegoro et al, 2016) albeit, with one exception (Accardo & Barrow, 2015). Notably, one study found that this relation held even after controlling for nonverbal IQ .…”
Section: Motor and Communication Developmentmentioning
confidence: 85%
“…This could be a pragmatic way to monitor and describe TTB during daily living activities in ASD subjects. Moreover, it is known that persistent TW in children with autism may contribute to secondary motor deformity by producing a shortening of the Achilles's tendon [Accardo et al, ], but it is not clear why some TTB subjects develop heel muscle shortening and others do not. A possible contributing factor could be the time the children spend in TTB during the day when they remain in a standing position.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in this study we found a directly proportional relationship between the presence of TTB and the severity of language delay in ASD children. Until recently, only a few authors suggested a possible relationship between these two elements [Accardo et al, ; Barrow et al, ], but systematic observations were never conducted, and no explanation has been provided. To our knowledge, this is the first study that analyzed, found and is able to confirm this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers described TW as intermittent or persistent (Ming et al, ), while others graded TW using history and observation (e.g., as absent, present in the past, intermittently present, or persistent) (Accardo & Barrow, ). As it is known that persistent TW in people with autism may contribute to secondary motor deformity by producing a shortening of the Achilles's tendon (Accardo, Monasterio, & Oswald, ) it becomes important to have an assessment tool and/or outcome measure for both the clinical and rehabilitative setting. Moreover, in a recent cohort study we observed that the condition is not necessarily related only to walking, since these children often also stand and run on their tiptoes.…”
Section: Introductionmentioning
confidence: 99%